APLIKASI BIOFLOK DAN PEMANFAATAN PROBIOTIK EM4 DALAM PAKAN PEMBESARAN IKAN LELE MUTIARA (Clarias gariepinus) - Madyasta Anggana Rarassari; Sefti Heza Dwinanti; Feldya D. Absharina; Zellica Gevira (JFMR (Journal of Fisheries and Marine Research), 2021)
Feed is an important factor in the success of cultivation, feed is also the component that costs the most that is about 70% of the total production cost. Therefore, it is necessary to do techniques that can increase production, one of which is by improving feed nutrition using EM4 probiotics. In addition, it can also be by applying bioflok technology that utilizes bacteria that can process aquaculture waste which is a problem in water quality into a continuously available source of fish feed. This study aims to find out if the application of bioflok and feed technology with EM4 can increase cultivation production. There are 3 treatments that will be used, namely, P1 (bioflok application), P2 (EM4 application), P3 (without bioflok and EM4). The fish used is pearl catfish seed (Clarias gariepinus) with a size of 6.5±0.5 cm with a dense spread of 150 heads / m3. Maintenance is carried out for 30 days (1 month) with the frequency of feeding